Investigation for Surface Quality Improvement of Barrel Finished FDM Patterns Based Vacuum Moulding - Singh, Rupinder; Singh, Manjinder (Asian Review of Mechanical Engineering, 2014)
In this paper investigations have been made for surface quality improvement of barrel finished fused deposition modelling (FDM) pattern based vacuum moulding (VM) components. VM master pattern was prepared using p- 430 grade bs on fdm setup (uPrint-SE), whose surface finish was improved by using barrel finishing (BF) process. The controllable parameters of bf and vm process (namely: media weight, cycle time, vacuum pressure and grain size of refractory sand) were studied at three levels by using taguchi L9 orthogonal array to find out their effects on dimensional accuracy of the final casting. Aluminium 6063 alloy was used for preparing VM components.